2007
DOI: 10.31729/jnma.283
|View full text |Cite
|
Sign up to set email alerts
|

Alcohols and other Substance Use/Abuse among Junior Doctors and Medical Students in a Teaching Institute

Abstract: abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
2
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 2 publications
4
28
2
3
Order By: Relevance
“…Nearly one third of females also had 'ever used' substance. 21 Similar findings were seen in other comprehensive study among medical students of BPKIHS by Shakya DR et al 22 Research in various aspects of alcohol and its ab/use Along with other studies, thesis studies/ researches of post-graduate and under-graduate students of BPKIHS are of special mention here because it caters 16 districts of eastern region not only as service area but also as teaching districts. Among the studies conducted on psycho-active substances, alcohol has naturally been the focus of attention.…”
Section: Alcohol Ab/use In Communitysupporting
confidence: 85%
“…Nearly one third of females also had 'ever used' substance. 21 Similar findings were seen in other comprehensive study among medical students of BPKIHS by Shakya DR et al 22 Research in various aspects of alcohol and its ab/use Along with other studies, thesis studies/ researches of post-graduate and under-graduate students of BPKIHS are of special mention here because it caters 16 districts of eastern region not only as service area but also as teaching districts. Among the studies conducted on psycho-active substances, alcohol has naturally been the focus of attention.…”
Section: Alcohol Ab/use In Communitysupporting
confidence: 85%
“…Our medical students and interns are reported to use psychoactive substances, not less but more than general people. 5 Our observations also show that health science students and professionals suffer more from mental ailments. [6][7] Physical problems are also reported higher, e.g.…”
Section: Dr Shakya Department Of Psychiatry Bp Koirala Institute Of supporting
confidence: 54%
“…2 However, the consumption of these substances is largely influenced by socio-demographic factors, education level, peer pressure, independent lifestyle, stressful activities, psychological factors and many more. [2][3][4] Our study showed the use of alcohol (75%), tobacco (40.9%) and marijuana (18.6%) was more prevalent among male students as compared to females. Shyangwa et al study in BPKIHS found 54.6% of male students drank alcohol.…”
Section: Resultsmentioning
confidence: 99%
“…6 Similarly, Shyangwa et al found junior residents were the highest (72%) user of alcohol and lowest being undergraduate medical students (31.7%). 3 A medical school is a vulnerable place where students may start to misuse various substances. Medical students have a burden full academic and clinical activity, easy access to substances that may catalyze the students to consume substances.…”
Section: Resultsmentioning
confidence: 99%